PENYULUHAN TEKNIK PERBANYAKAN DAN PENGEMASAN LEBAH MADU (TRIGONA SP.) DI KECAMATAN BARUGA, KOTA KENDARI - Ilma Sarimustaqiyma Rianse; Fahria Nadiryati Sadimantara; Wa Kuasa Baka; Yusuf Musafir Kolewora; Muhammad Iqbal Kusumabaka Rianse; Ida Mardhiah Afrini Kasman Arifin; Awaluddin Awaluddin; Waode Siti Anima Hisein (Jurnal Pengabdian NUSANTARA, 2023)
Extension of Propagation and Packaging Techniques for Honey Bees (Trigona sp.) In Baruga District, Kendari City. Community Partnership Program Faculty of Agriculture University of Halu Oleo Kendari with one of the partners of Mataiwoi Farmers Group Baruga District Kendari City has carried out community service in order to provide encouragement, spirit to horticulture farmers and plantation crops in increasing Trigona sp. honey bee business in increasing productivity. Implementation of the Community Partnership Program is very appropriate as a means and media for technology transfer how to increase the productivity of farmer groups Method of Implementation PKM activities are carried out on the basis of observations and problems found in the field. From the implementation of this program the output targets achieved from the implementation of the program are: (1) Farming partners master the techniques of propagation and removal of colonies of Trigona sp., Which are based on their ecological rules (2) Farmers know there are ways to make bees that honey bees enjoy Trigona sp. (3) Farming partners can know how to harvest Trigona sp., Which is good and hygienic (4) Farmers can package honey that is worth selling by standardizing the relevant institutions so that the resulting honey product is more acceptable to consumers because of the consumer awareness about safer products is getting better